Quorum sensing-controlled buoyancy through gas vesicles: Intracellular bacterial microcompartments for environmental adaptation - Ramsay, Joshua (Landes Bioscience, 2012)
Gas vesicles are gas-filled microcompartments produced by many cyanobacteria and haloarchaea to regulate buoyancy and control positioning in the water column. Recently we identified the first case of gas vesicle production by a member of the Enterobacteriaceae, Serratia sp ATCC39006. Gas vesicle production enabled colonisation of the air-liquid interface and was positively regulated in low-oxygen conditions, suggesting development of these intracellular organelles is an adpative mechanism facilitating migration to the water surface. Vesicle production was also regulated by the intercellular communication molecule N‑butanoyl-L‑homoserine lactone (BHL) showing that gas vesicle production is controlled at the population level, through quorum sensing, with BHL acting as a morphogen. Gas vesicle production was also reciprocally regulated with flagella-driven swarming motility by the global regulatory protein RsmA, suggesting a fork in the regulatory pathway that controls induction of these distinct modes of mobility. Here we discuss these findings in the context of the interesting physiology of Serratia 39006 and highlight future prospects for gas vesicle research in this highly tractable strain.